Complete web monitoring - Croll, Alistair (O'Reilly, 2009)
Discover how visitors use and interact with your site through web analytics, segmentation, conversions, and user interaction analysis. Find out your market's motivations with voice-of-the-customer research. Measure the health and availability of your website with synthetic testing and real-user monitoring. Track communities related to your online presence, including social networks, forums, blogs, microblogs, wikis, and social news aggregators. Understand how to assemble this data into clear reports tailored to your organization and audience.